High Resolution Imaging Using Micro-Objectives Fabricated by 2-Photon-Polymerization - Fabian Thiemicke; Mostafa Agour; Ralf B. Bergmann; Claas Falldorf (Applied Sciences)
We experimentally demonstrate high-resolution imaging using micro-objectives fabricated by two-photon polymerization (2PP) lithography, highlighting its potential as a flexible and precise fabrication method. The 2PP manufacturing process offers the ability to develop micro-optics with customized geometries and material properties, including tailored refractive indices. This flexibility introduces new degrees of freedom in optical system design and expands the applicability of micro-optics to advanced imaging tasks where other materials and fabrication methods are insufficient. For our study, bi-convex micro-optics with different geometries with radii of curvature of <15 <semantics>μ</semantics>m and minimized contact areas (<1 <semantics>μ</semantics><semantics>m2</semantics>) to ensure easy release from the substrate were fabricated with 2PP and investigated for their optical performance. With these micro-optics, the tracks with a pitch of 320 nm and the pits and lands as small as 130 nm were successfully resolved on a BluRay disc surface, demonstrating for the first time the high-resolution imaging capabilities of bi-convex spherical micro lenses.